PELAYANAN PENGGUNAAN IDENTITAS KEPENDUDUKAN DIGITAL (IKD) DI DUKCAPIL KABUPATEN MERANGIN - Hesti Kurnia Hesti; Hasmawati; Eko Wulandari Eko; sukur (AbdiMasya | Hira Institute, 2025)
This study examines the impact of using Digital Population Identity (IKD) on the effectiveness of civil registration and vital statistics (Dukcapil) services in Merangin Regency. The research highlights key issues such as the transition from manual to digital identity systems, public awareness, and system readiness within local government agencies. The primary objective is to determine whether the implementation of IKD enhances service delivery, particularly in terms of speed, accuracy, and accessibility. A quantitative approach was employed using a survey method with a structured questionnaire distributed to IKD users and Dukcapil staff. Data were analyzed using descriptive statistics and regression analysis. The findings indicate a significant positive correlation between the use of IKD and improved service effectiveness. IKD implementation has led to faster processing times, reduced administrative errors, and increased user satisfaction. However, challenges remain in terms of digital literacy and infrastructure. The study concludes that while IKD positively influences service quality, further efforts are needed to ensure inclusive and sustainable digital transformation in public administration.